Assessing the Effect of Simultaneous Combining of Transcranial Direct Current Stimulation and Transcutaneous Auricular Vagus Nerve Stimulation on the Improvement of Working Memory Performance in Healthy Individuals - Zhao, Rui; He, Zhao-Yang; Cheng, Chen; Tian, Qian-Qian; Cui, Ya-Peng; Chang, Meng-Ying; Wang, Fu-Min; Kong, Yao; Deng, Hui; Yang, Xue-Juan; Sun, Jin-Bo (Frontiers in Neuroscience, 2022)
Previous study found that combining transcranial direct current stimulation (tDCS) and transcutaneous auricular vagus nerve stimulation (taVNS) could evoke significantly larger activation on a range of cortical and subcortical brain regions than the numerical summation of tDCS and taVNS effects. Here, two within-subject experiments were employed to investigate its effects on working memory (WM). In experiment 1, the WM modulation effects of tDCS over left dorsolateral prefrontal cortex (DLPFC), taVNS, and stimultaneous joint simulation of tDCS over left DLPFC and taVNS (SJS-L) were compared among sixty healthy subjects. They received these three interventions between baseline test and post-test in random orders by three times. In spatial 3-back task, there was a significant interaction between time and stimulations in the accuracy rate of matching trails (mACC, p=.018). MACC were significantly improved by SJS (p=.001) and taVNS (p=.045), but not by tDCS (p=.495). Besides, 41 subjects in SJS group showed improvements, which was significantly larger than taVNS group (29 subjects) and tDCS group (26 subjects). To further investigate the generalization effects of SJS, 72 students were recruited in experiment 2. They received tDCS over right DLPFC, taVNS, stimultaneous joint simulation of tDCS over right DLPFC and taVNS (SJS-R), and sham stimulation in random orders by four times. No significant results were found but there was a similar tendency with experiment 1 in spatial 3-back task. In conclusion, combining tDCS and taVNS might be a potential non-invasive neuromodulation technique which is worthy of study in the future.